p53 deficiency mediates cisplatin resistance by upregulating RRM2 and crotonylation of RRM2K283 through the downregulation of SIRT7 - Sun, Liangjie; Li, Yi; Wang, Meng; Luo, Lan; Sun, Ruiqing; Chen, Yang; Bai, Yan; Ding, Chong; Wang, Yixiang (Frontiers in Molecular Biosciences, 2024)
p53 deficiency plays a crucial role in chemotherapy resistance through various biological events, including posttranslational modifications (PTMs). Recently, lysine crotonylation (Kcr) has been shown to play a vital role in cancer progression. However, the global p53-regulated crotonylome and the function of these altered Kcr proteins after p53 deficiency remain unclear. In this study, we used a SILAC-based quantitative crotonylome to identify 3520 Kcr in 1924 crotonylated proteins in response to p53 knockout. We found that increased crotonylation of RRM2 at K283 (RRM2 K283Cr ) in the presence of p53 deficiency promoted HCT116 cell resistance to cisplatin. We discovered that SIRT7 could be the decrotonylase of RRM2 and was downregulated after p53 knockout, resulting in increased RRM2 K283Cr . Mechanistically, p53 deficiency inhibited cell apoptosis by upregulating RRM2 protein expression and RRM2 K283Cr -mediated cleaved-PARP1 and cleaved-caspase3 expression, and SIRT7 was downregulated to upregulate crotonylation of RRM2 upon p53 deficiency. In conclusion, our results indicated that p53 deficiency plays a malignant role in colon cancer resistance to cisplatin therapy by regulating RRM2 protein and RRM2 K283Cr expression. Our findings provide a novel therapeutic target against p53-deficient cancer.